Cytochrome c Oxidase on the Crossroads of Transcriptional Regulation and Bioenergetics - Chicherin, Ivan Vladimirovich; Dashinimaev, Erdem; Baleva, Mariia; Krasheninnikov, Igor; Levitskii, Sergey; Kamenski, Piotr (Frontiers in Physiology, 2019)
Mitochondria are the organelles of eukaryotic cells responsible for the ATP production by means of the electron transfer chain. Its work is under strict genetic control providing the correct assembly of the enzyme complexes and the interface to adapt the energetic demands of the cell to the environment. These mechanisms are particularly developed in the cells with high energy consumption, like neurons and myocytes. This review summarizes several aspects of the involvement of the electron transfer chain complexes in the transcriptional control mechanisms of the neurons and other cells. Their influence on the differentiation of neurons is also discussed.